INTEGRATED CASH FLOW ANALYSIS OF A REGIONAL MEDICAL TREATMENT FACILITY IN THE REPUBLIC OF TATARSTAN - Guzel Khalitovna Zinurova (Science and Innovation Center Publishing House, 2020)
The current problem of financial management optimization in Publicly Funded Health Facilities is examined. In line with the state policy, it is essential to clearly define the limits of social safety net funded by state budgets and to develop new social protection mechanisms. The implementation of the above largely depends on the status and stability of the state and municipal finances, which are the primary source of funding.